Atypical presentation of a large cervical schwannoma - Singh, Inderdeep; Singh, Anubhav (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Hypoglossal nerve schwannomas are rare benign tumors arising from the schwann cells covering the hypoglossal nerve. These tumors are slow growing and their symptoms are usually due to pressure effects over the adjacent structures. We present a rare case of a large intracranial and cervical schwannoma arising from the hypoglossal nerve. We discuss the atypical presentation and vague symptoms with which a patient of hypoglossal schwannoma may present. Surgery in such cases requires the joint efforts of the team of Neurosurgeons and Otorhinolaryngology and Head and Neck surgeons.